Measurement of roller load, load variation, and lubrication in a wind turbine gearbox high speed shaft bearing in the field. (August 2020) - Nicholas, G.; Howard, T.; Long, H.; Wheals, J.; Dwyer-Joyce, R.S.
Abstract: The variability of applied load and the integrity of lubrication are crucial factors dictating the durability of wind turbine gearbox bearings. In this work, new ultrasonic reflectometry techniques have been implemented to measure both load and lubrication in the high-speed shaft bearing of a field operational Vestas V42 wind turbine gearbox. Miniature piezoelectric transducers were bonded onto the bearing outer raceway. The reflected pulses were used to infer bearing load and lubrication. Roller load measurements were seen to vary by 33% across the roller complement, with similar trend observed for reflection coefficient. Inspection of the reflection coefficient patterns were able to show whether the roller inlet region was fully flooded or partially starved, capturing the stochastic behaviour of bearing lubrication. Highlights: A wind turbine high-speed shaft bearing was instrumented with ultrasonic sensors. Bearing load and raceway lubrication were successfully inferred from the signals. Lubricant film generated and load carried by the same roller within a complement is consistent with each revolution. Load variation exist for rollers across the complement. Two lubrication reflow behaviours observed at low and high bearing rotational speeds.